Triple Cs of self-directed learning: Concept, conduct, and curriculum placement - Dinesh Kumar Badyal; Hem Lata; Monika Sharma; Anjali Jain Jain (Wolters Kluwer Medknow Publications, 2020)
Self-directed learning (SDL) is one of the teaching-learning methods that can be used in medical education at all levels. The use of SDL in undergraduate (UG) teaching is becoming common due to the implementation of competency-based education in many countries. The new competency-based UG medical curriculum in India includes lifelong learning skills as one of the major components. The SDL method is reported to increase the lifelong learning skills of students. The concept of SDL is based on experiential learning and its conduct needs proper understanding of the concept. The conduct can include two contact sessions and an intersession or gap period of few days. The contact sessions focus on introduction, facilitation, and debriefing. The intersession period is the real learning period for the students. SDL also includes the use of various assessment methods. All SDL sessions are followed by an evaluation of various stakeholders. Advancements in information technology (IT) and the advent of many innovations in teaching can be aptly used in SDL conduct and evaluation. The present coronavirus disease 2019 (COVID-19) pandemic has further provided opportunity to use IT in the new normal post-COVID-19 times. Curriculum placement must be done in alignment with other teaching-learning methods. Training of facilitators, availability of resources, and preplanning help in successful SDL conduct. If implemented appropriately, SDL can be a great method to help students in their postinstitute lives.